Chemical study of the macrophyte duckweed (Lemna minor L.) - Vera, José; Gavin-Moyano, César; Villamar, Mónica; Ortiz, Jhonny; Sevilla, Jaime; Lucas, Leonel; García, Byron (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2024)
Duckweed (Lemna minor L.) has attracted considerable attention in the scientific field due to its nutritional contribution and capacity to phytoremediate waters. Therefore, the objective of the study was to analyze the chemical composition of the macrophyte (Lemna minor) from natural environments. Chemical compounds and Weende composition were determined from the plant, and the fresh weight gain was observed in different types of water (deep well and bovine slurry), waters that were subjected to physical-chemical analysis. The chemical analysis of the macrophyte resulted in the presence of 1.42 mg.g-1 of total chlorophyll; 2.35 mg.kg-1 of ascorbic acid; tannin content less than 2.50 mg.kg-1; 45.34 mg.kg-1 of phenols; also the presence of alkaloids, phenols and reducing sugars in the chemical screening. The Weende analysis indicates a composition of: 89 % of dry matter, 30 % of crude protein, 4 % of gross energy, 3.2 % of ether extract, 15 % of ashes, 32 % of nitrogen-free extract and 10 % of fiber. The fresh weight gain of Lemna minor obtained in water contaminated with bovine slurry increased significantly 13 g.day.m3 and 5 g.day.m3 in deep well water. The physical-chemical properties of the water improve their quality 16 days after treatment with this aquatic plant with respect to the initial analysis. This macrophyte exhibits remarkable phytoremediation properties to absorb, metabolize and stabilize various pollutants effective in the purification of contaminated waters.